Safe haven investment during turbulent conditions in Indonesia and Philippines capital market - Pemayun, A.A. Gde Ari Widhiasmana; Yasa, Gerianta Wirawan (International research journal of management, IT and social sciences, 2020)
Haven investment is a safe and profitable asset for investors during turbulent capital market conditions. Investors tend to divert investment in shares owned to safe-haven assets to secure investment value during the decline in value on the stock market. This study aims to obtain empirical evidence related to the ability of gold as a safe-haven investment in the State of Indonesia and the ability of gold as a safe-haven investment in the Philippines. The data used in this study is a daily return from the period January 1, 2018, to February 20, 2020. Data analysis techniques used in this study use the Augmented Dickey-Fuller (ADF) stationary test and the quantile regression analysis test with a quintile rate of 50%, 40%, 30%, 20%, and 10%. The results show that gold is a haven investment in Indonesia. Gold is a haven investment in the Philippines.